2022
DOI: 10.3390/ijms232314575
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Susceptibility and Resilience to PTSD: Role of Dopamine Metabolism and BDNF Expression in the Hippocampus

Abstract: Susceptibility and resilience to post-traumatic stress disorder (PTSD) are recognized, but their mechanisms are not understood. Here, the hexobarbital sleep test (HST) was used to elucidate mechanisms of PTSD resilience or susceptibility. A HST was performed in rats 30 days prior to further experimentation. Based on the HST, the rats were divided into groups: (1) fast metabolizers (FM; sleep duration < 15 min); (2) slow metabolizers (SM; sleep duration ≥ 15 min). Then the SM and FM groups were subdivided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
2
3
0
3
Order By: Relevance
“…Interestingly, trans -resveratrol (RES), a natural polyphenol belonging to the phytoalexins similar to SSRIs, has been found to downregulate the mRNA expression of 5-HT transporter in the hippocampus [ 28 ]. Recent studies have shown that RES can alleviate anxiety-like behavior and decrease brain-derived neurotrophic factor (BDNF) levels, which are typically decreased in stressed rats in experimental PTSD models [ 29 , 30 ]. It is worth noting that PTSD-resilient rats exhibit increased hippocampal BDNF mRNA levels along with simultaneous increases in DOP (DAT) transporter mRNA levels in the hippocampus [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, trans -resveratrol (RES), a natural polyphenol belonging to the phytoalexins similar to SSRIs, has been found to downregulate the mRNA expression of 5-HT transporter in the hippocampus [ 28 ]. Recent studies have shown that RES can alleviate anxiety-like behavior and decrease brain-derived neurotrophic factor (BDNF) levels, which are typically decreased in stressed rats in experimental PTSD models [ 29 , 30 ]. It is worth noting that PTSD-resilient rats exhibit increased hippocampal BDNF mRNA levels along with simultaneous increases in DOP (DAT) transporter mRNA levels in the hippocampus [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that RES can alleviate anxiety-like behavior and decrease brain-derived neurotrophic factor (BDNF) levels, which are typically decreased in stressed rats in experimental PTSD models [ 29 , 30 ]. It is worth noting that PTSD-resilient rats exhibit increased hippocampal BDNF mRNA levels along with simultaneous increases in DOP (DAT) transporter mRNA levels in the hippocampus [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Наиболее известной, хорошо валидированной и приближенной к клинике экспериментальной моделью ПТСР является предаторный стресс (ПС) у грызунов [16]. Эта модель позволяет разделить животных на высоко-и низкотревожных для изучения возможных механизмов устойчивости к стрессу [17][18][19][20]. ПС моделируют путем экспозиции крыс к запаху кошачье мочи или виду кошки на 10-15 мин в день в течение 10 дней.…”
unclassified
“…Эти параметры используются для расчета индекса тревожности, разработанного Cohen с соавт. [16] и широко используемого в моделях ПТСР [17][18][19][20][21].…”
unclassified
See 1 more Smart Citation